2016
DOI: 10.3390/app7010012
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Lactones with Methylcyclohexane Ring and Their Biological Activity

Abstract: Abstract:The aim of the study was to obtain biological active compounds during biotransformation. Three bicyclic halolactones with methylcyclohexane ring (2-chloro-4-methyl-9-oxabicyclononan-8-one, 2-bromo-4-methyl-9-oxabicyclo[4.3.0]nona--8-one and 2-iodo-4-methyl-9-oxabicyclo[4.3.0]nonan-8-one) obtained from the corresponding γ,δ-unsaturated acid were subjected to a screening biotransformation using 22 fungal strains. Two of these strains (Cunninghamella japonica AM472 and Fusarium culmorum AM10) were able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…The lack of products derived from chlorolactone 4 was, therefore, not surprising. Bromo-and iodolactones are much more frequently transformed by filamentous fungi [19][20][21][22]. Such a dependence can be seen here as well.…”
Section: Preparative Biotransformation Of Halolactones 5 and 6 Analys...supporting
confidence: 70%
See 1 more Smart Citation
“…The lack of products derived from chlorolactone 4 was, therefore, not surprising. Bromo-and iodolactones are much more frequently transformed by filamentous fungi [19][20][21][22]. Such a dependence can be seen here as well.…”
Section: Preparative Biotransformation Of Halolactones 5 and 6 Analys...supporting
confidence: 70%
“…In our research, we used lactones containing halogen atoms in the molecule of substrates. Previous studies carried out so far showed [18][19][20][21][22][23][24] that filamentous fungi, especially those belonging to the genera Fusarium and Absidia, can carry out the hydrolytic dehalogenation of halolactones. As a result, hydroxylactones with a different conformation than halolactones obtained by chemical synthesis were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…However, lactone compounds' antibacterial activity depends on if the structure contains substituent fluorine and the length of the bacterial lipopolysaccharide (Kowalczyk et al, 2021). As such, unsaturated and hydroxy lactone compounds have antibacterial activity against S. aureus (Wińska et al, 2018). -lactone compounds also show antibacterial activity (Mazur & Maslowiec, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…All lactones, both substrate and biotransformation products, were able to inhibit the growth of the S. aureus strain. Complete inhibition was observed for lactones 90a – c , and lactone 91 ( Figure 13 ) showed a slight inhibition on the growth of this strain together with a significant extension of the adaptive phase (20–36 h) [ 89 ].…”
Section: Biotransformations As a Methods For Obtaining New Lactone De...mentioning
confidence: 99%